Vortex Fluidics Improved Morphology of CH3NH3PbI3-xClxFilms for Perovskite Solar Cells - Jutarat Sudchanham (2018)
© 2017 Wiley-VCH Verlag GmbH & Co. KGaA, Weinheim We report the use of a vortex fluidic device (VFD) to prepare the precursor solution for CH3NH3PbI3-xClxperovskite films. These films exhibited improved surface coverage and enhanced light absorption relative to conventional batch processing used for preparing the precursor solution. This VFD-assisted perovskite solar cell displayed a power conversion efficiency of 11.65 %, which is significantly higher than 9.26 % of the control device.